Efecto de la temperatura del sustrato sobre la estructura y propiedades ópticas de películas delgadas de Zno:Al crecidas por rociado pirolítico - Velarde Hurtado, Luis Gerardo (2017)
In this work, the optical and structural properties of ZnO thin lm doped with aluminum_x000D_ (ZnO:Al) grown by spray pyrolysis by e ect of the temperature of the substrate was_x000D_ evaluated. Were used as precursor solution Zinc Acetate [Zn(CH3CO2)2;2H2O] dissolved_x000D_ in ethanol and aluminum chloride [AlCl3;6H2O] as doping solution dissolved in ultrapure_x000D_ water. Varying substrate temperature was 250 oC to 500 oC, keeping the concentration_x000D_ constant doping to 4% Al atoms. The structural properties of the thin lm grown were_x000D_ characterized by X-Ray Di raction (XRD) and optical transmittance properties were_x000D_ studied using UV-visible (Uv-vis) spectroscopy absorption, in addition an analysis by_x000D_ Scanning Electron Microscopy. The rst study con rmed the stable structural nature of_x000D_ ZnO as Wurtzita hexagonal, with a preferential orientation in the [002]. It was observed_x000D_ that the quality of the crystal structure of the grown thin lm improved with increasing_x000D_ temperature of the substrate, and consequently favoring the optical transmittance in the_x000D_ visible region. It was found that the best value in the optical transmittance greater to the_x000D_ 90% occurs at a temperature of 400 oC, thus demonstrating the feasibility of the pyrolysis_x000D_ spray technique